Calcium Signaling in Mammalian Eggs at Fertilization - Shirakawa, Hideki; Kikuchi, Takashi; Ito, Masahiko (Current Topics in Medicinal Chemistry, 2016)
The innovation and development of live-cell fluorescence imaging methods have revealed the dynamic aspects of intracellular Ca2+ in a wide variety of cells. The fertilized egg, the very first cell to be a new individual, has long been under extensive investigations utilizing Ca2+ imaging since its early days, and spatiotemporal Ca2+ dynamics and underlying mechanisms of Ca2+ mobilization, as well as physiological roles of Ca2+ at fertilization, have become more or less evident in various animal species. In this article, we illustrate characteristic patterns of Ca2+ dynamics in mammalian gametes and molecular basis for Ca2+ release from intracellular stores leading to the elevation in cytoplasmic Ca2+ concentration, and describe the identity and properties of sperm-borne egg-activating factor in relation to the induction of Ca2+ waves and Ca2+ oscillations, referring to its potential use in artificial egg activation as infertility treatment. In addition, a possible Ca2+ influx-driven mechanism for slow and long-lasting Ca2+ oscillations characteristic of mammalian eggs is proposed, based on the recent experimental findings and mathematical modeling. Cumulative knowledge about the roles of Ca2+ in the egg activation leading to early embryogenesis is summarized, to emphasize the diversity of functions that Ca2+ can perform in a single type of cell.
Keywords: Egg activation